2021
DOI: 10.1002/hyp.14032
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic prediction model for time‐to‐peak

Abstract: A simplified empirical equation is developed for widespread prediction of dynamic catchment response time. This model allows for time-to-peak prediction to evolve from static, lumped models, thereby providing a single value for any storm within a given catchment, using a single set of input parameters, that can be applied to a dynamic model, thus accounting for the variability between storm sizes and catchment moisture conditions. These dynamic prediction methods are translated to North America for the first t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Thus, shallow flows resulting from relatively small runoff events will be slow. This may be why the equation of Langridge et al (2021), which includes representations of the climate and the peak discharge, performed relatively well in this study. Cen et al (2022) found that unit discharge was the most important factor in determining the transition from laminar to transitional flows, in flume experiments using synthetic vegetation.…”
Section: Darcy-weisbach Roughness Coefficient Fmentioning
confidence: 66%
See 4 more Smart Citations
“…Thus, shallow flows resulting from relatively small runoff events will be slow. This may be why the equation of Langridge et al (2021), which includes representations of the climate and the peak discharge, performed relatively well in this study. Cen et al (2022) found that unit discharge was the most important factor in determining the transition from laminar to transitional flows, in flume experiments using synthetic vegetation.…”
Section: Darcy-weisbach Roughness Coefficient Fmentioning
confidence: 66%
“…According to Langridge et al (2021), "wet" basins have R c values greater than or equal to 0.7; basins having R c values less than 0.5 are classified as "dry". Values of C 1 and C 2 are provided for "wet", "average" and "dry" basins in seasons which are assumed to be "Wet" (December through March), "Dry" (June through September) and "Average" (April, May, October, and November).…”
Section: Response Times From Existing Empirical Equationsmentioning
confidence: 99%
See 3 more Smart Citations